Students’ Attitudes towards Group Collaborative Learning Experiences: A Case of University of Eastern Africa, Baraton - Makewa, Lazarus Ndiku; Dorcas, Mukami; Baraka, Ngussa; Samuel, Njoroge; Joshua, Kuboja (Advances in Social Sciences Research Journal, 2015)
This piece of work investigated students’ attitudes towards group collaborative learning experiences and frustration. The study also sought to find out the relationship that existed between the student’s gender, year of study, courses registered that semester, the number of hours dedicated to group collaborative learning per week with the students mean attitudes towards collaborative learning. The study established that most of respondents liked participating in collaborative working experiences, had great preference to work in collaboration with others, viewed collaborative learning experience as important except those in their second year of study who did not rate collaborative learning as very important, and tended to agree that they learned more in group than alone. It is therefore recommended that in the course of the lesson, teachers set time for group work to motivate the learners, not only interacting with the content, but also with the group members.